ASUHAN KEPERAWATAN PADA NY. A (G2P1A0) DENGAN ANEMIA DI LINGKUNGAN CIMANGGIS - Nur'Aini (2022)
Anemia is a condition in which red blood cells decrease, causing the oxygen-carrying capacity of the vital organs of pregnant women and fetuses to decrease. Anemia that occurs in pregnant women in developing countries generally occurs due to iron deficiency. Pregnant women with anemia have the opportunity to experience bleeding during childbirth which can cause death. One of the factors in the maternal mortality rate (MMR) is the occurrence of bleeding during childbirth which is characterized by anemia during pregnancy. The purpose of this study was to provide nursing care to pregnant women, Mrs. A (G2P1A0) with anemia in the Cimanggis environment. This research design uses qualitative research methods by conducting interviews, observations, and documentation on clients directly with a sample of 1 respondent. The results of the study showed that most pregnant women with anemia had signs and symptoms, one of which was easily tired when doing physical activities, unhealthy sleep patterns, and anxiety. Therefore, it can be said that the relationship between anemia in pregnant women and patterns of physical activity, sleep patterns and anxiety are interrelated. It is expected that nurses as health workers can provide health education to pregnant women with anemia in order to increase the knowledge of pregnant women about the risk of anemia during pregnancy.